1977
DOI: 10.1136/jech.31.3.148
|View full text |Cite
|
Sign up to set email alerts
|

A case control study of carcinoma of the ovary.

Abstract: SUMMARY There is increased concern over the apparent rise in incidence of patients with carcinoma of the ovary, particularly in older women. In an attempt to identify aetiological factors 300 women with cancer of the ovary diagnosed at laparatomy were studied. A questionnaire was administered to these women (Group A) and to two control groups matched by age. The first control group (Group B) comprised patients in a gynaecological ward and the second (Group C) comprised women on the lists of general practitione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
70
1
6

Year Published

1981
1981
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 7 publications
5
70
1
6
Order By: Relevance
“…Our finding of no overall relationship between hormone replacement therapy and ovarian cancer supports those of other investigators (Newhouse et al, 1977;Hildreth et al, 1981;Weiss et al, 1982). An increased risk associated with the therapy was found among women who reported hysterectomy, but the finding was based on very few cases and may have been due to chance.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our finding of no overall relationship between hormone replacement therapy and ovarian cancer supports those of other investigators (Newhouse et al, 1977;Hildreth et al, 1981;Weiss et al, 1982). An increased risk associated with the therapy was found among women who reported hysterectomy, but the finding was based on very few cases and may have been due to chance.…”
Section: Discussionsupporting
confidence: 82%
“…The raised risk for women with a first pregnancy after 35 years persisted (RR = 3.9, 95% CI 1.1-14.2). Results from other studies regarding the risk for women having a first child at relatively older ages are inconclusive, some finding no association (Newhouse et al, 1977;Casagrande et al, 1979;Cramer et al, 1983;Lesher et al, 1985), others an increased risk (Joly et al, 1974;McGowan et al, 1979;Hildreth et al, 1981;Franceschi et al, 1982). Only Franceschi et al (1982) found the increased risk to be statistically significant and independent of parity.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Evidence from several case-control studies conducted mainly in North America (McGowan et al, 1979;Annegers et al, 1979;Hildreth et al, 1981;Weiss et al, 1981;Willett et al, 1981;Rosenberg et al, 1982;Cramer et al, 1982;Casagrande et al, 1983; Centers for Disease Control Cancer and Steroid Hormone Study, 1983; see also Newhouse et al, 1977) suggests that the use of cQmbined oral contraceptives (OCs) reduces the risk of epthelial ovarian cancer. General lifestyle and reproductive characteristics, however, are notoriously different in Italy.…”
mentioning
confidence: 99%
“…In most epidemiological reviews, ovarian cancer is considered as one disease, although some recent ones have categorised the cases as epithelial and non-epithelial (Newhouse et al, 1977;Greene et al, 1984). But within those of epithelial origin, different pathological diagnoses can also be analysed separately.…”
mentioning
confidence: 99%